Leadership in Support of Teachers’ Action Research in Schools: Heads of Departments Positioned for Purpose - Augustin, Désirée S. (School of Education, UWI, 2020)
Participation by secondary school teachers in an in-service Diploma in Education (Dip. Ed.) programme at one university site in Trinidad and Tobago requires untrained teachers to juggle the roles of full-time teacher in their schools and part-time students seeking professional certification. In conducting action research under these circumstances, student-teachers need support. Data gathered via an online survey provided information on the support (or lack thereof) that student-teachers received from the Head of Department (HoD) while they conducted research during the programme. Using a focused stratified purposeful sampling strategy to ascertain further the nature of support provided by the HoD, I interviewed 5 student-teachers via telephone. Drawing on the work of Kaldi and Xafakos (2017) and Seider and Lemma (2004), I analysed teachers’ responses. Data revealed that the personality of the HoD, the relationship between the HoD and teacher, and the nature of involvement of the HoD served as contributors to the psychological, pedagogical and administrative support provided by the HoD. Teachers recommended strategies for enhancing a supportive leadership role for the HoD. Recommendations based on the study include a conceptualisation of the HoD as mentor and coach; engagement in deliberate efforts to enhance communication and collaboration among key stakeholders; addressing the policy context in which the HoD and teacher function; and engaging HoDs in meaningful professional development.
Keywords: Action Research in School; Teacher Inquiry; Middle Leadership; Heads of Departments; Mentoring; Coaching